EFFECT OF CYSTEIN HYDROCHLORIDE AND VITAMIN E SUPPLEMENTATION ON QUALITY OF CRYOPRESERVED HARIANA BULL SEMEN - SINGH PAL, AJENDAR; SINGH, VIJAY; PATEL, AKHIL (The Indian Journal of Animal Reproduction, 2022)
The present study was aimed to evaluate the beneficial effects of supplementation of cystein hydrochloride andVitamin E on seminal attributes during different stages of semen cryopreservation in Hariana bull. Thirty two ejaculatesfrom four Hariana bulls were collected after initial examination the qualified ejaculates were divided into three aliquots;one aliquot was extended with glycerolated egg yolk tris citrate (GEYT) extender (Control), second aliquot was extendedwith GEYT supplemented with Cystein hydrochloride @ 5.0 mM (T1) and the third aliquot was extended with GEYTsupplemented with VitaminE @ 2.5 mM (T2). All semen samples were equilibrated and cryopreserved. The effect ofcystein hydrochloride and vitamin E was determined by assessment of sperm viability, progressive motility, hypoosmoticresponse, and acrosomal integrity at three stages i.e. after dilution, pre-freeze and post –thaw. It was observedthatsupplementation of cysteine hydrochloride (5mM) and vitamin-E (2.5 mM) caused significant (P
Keywords: Bull; cryopreservation; cystein hydrochloride; vitamin c; semen